Kepemimpinan Kepala Sekolah Dasar Pada Era Revolusi Industri 4.0 dan Pandemi Covid 19 - I Wayan Sudika (STAHN Mpu Kuturan Singaraja, 2020)
The era of 4.0 industrial revolutions is marked by growing up of information technology or digital technology. The headmaster as a leader must adjust the leadership style according to the demands and changes that occur. Effectively the leadership, if a leader is able to combine situations and conditions with his or her pattern of behavior or leadership style. In the era of 4.0 industrial revolutions as a leader, the headmaster of elementary schools (elementary schools) must have the ability to use digital technology, in carrying out its duties and functions. Impact of Covid 19 pandemic is very remarkable, not only affected on one sector of human life, but affected for all sectors, including education; the learning process will be done with daring method. In the situation of the Covid-19 pandemic, primary school headmaster are required to have the ability to carry out crisis management, which is based on the respectfully of soul and loyalty realized through empathy. Keywords: The Leadership, 4.0 industrial revolution, Covid-19